(untitled) (Revista LIDER, 2020)
The numerous and powerful studies on the Common Goods in Latin America tend to have a marked Capitalist and Eurocentric character. Faced with this, various proposals aim to understand the problems arising from these discussions from a different point of view, constituting the emerging bases of a critical paradigm as a decolonization of these dominant approaches. This paper analyzes some of these efforts from Bolivia and Mexico, which have an overall regional vision for Latin America. We conclude that there is still a way to build a Latin American critical paradigm of the Common Goods and we offer some ideas that can contribute to this important task.